THE DIFFERENCE OF ABNORMAL RETURN AND TRADING VOLUME ACTIVITY SHARE BEFORE RAMADAN, DURING RAMADAN, AND AFTER RAMADAN: STUDY ON LQ45 COMPANIES LISTED IN BEI PERIOD 2018 - 2019 - Brilliant Yudha Muhammad; ika yanuarti (Universitas Multimedia Nusantara, 2019)
Introduction/Main Objectives: This study aims to analyze differences in abnormal return and trading volume activities before Ramadhan, during Ramadhan, and after Ramadhan in LQ45 companies in the period 2018 - 2019. Background Problems: Ramadan anomaly is a strategy that is contrary to the efficient market, because this strategy can produce abnormal returns and high trading volume activity around Ramadan that can be utilized for investment decision making. Novelty: Capital market participants not only see the company's performance in investment decision making, but also see the market anomalies that occur around Ramadan. Research Methods: Samples taken by using purposive sampling as many as 37 companies. The data analysis technique starts with conducting a normality test using Kolmogorov-Smirnov, transforming data, then testing the hypothesis using a paired t-test. Finding/Results: (1) There is a difference in abnormal return before Ramadan and during Ramadan 2019, during Ramadan with after Ramadan 2019, and during Ramadan with after Ramadan 2018. (2) There is no difference in abnormal return before Ramadan and after Ramadan 2019, before Ramadan with during Ramadan 2018, and before Ramadan and after Ramadan 2018. (3) There are differences in trading volume activity before Ramadan during Ramadan 2018, and during Ramadan with after Ramadan 2018. (4) There is no difference in trading volume activity before Ramadan with Ramadan 2019, during Ramadan with after Ramadan 2019, before Ramadan with after Ramadan 2019, and during Ramadan with after Ramadan 2018. Conclusion: Different research results show that the abnormal return reaction and trading volume activity are not consistent with the Ramadan.